2001
DOI: 10.1016/s0969-2126(00)00559-1
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrophobin EAS Is Largely Unstructured in Solution and Functions by Forming Amyloid-Like Structures

Abstract: EAS joins an increasing number of proteins that undergo a disorder-->order transition in carrying out their normal function. This report is one of the few examples where an amyloid-like state represents the wild-type functional form. Thus the mechanism of amyloid formation, now thought to be a general property of polypeptide chains, has actually been applied in nature to form these remarkable structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 46 publications
(10 reference statements)
1
121
1
Order By: Relevance
“…Several algorithms have been developed with the goal of predicting regions of protein sequence that have a high propensity for forming amyloid-like β-sheet polymeric structures. Given the evidence from X-ray fiber diffraction, electron microscopy, and Congo red and Thioflavin-T (ThT) binding that rodlets formed by class I hydrophobins are amyloid-like (15,16), we analyzed the amino acid sequence of EAS using several of these algorithms. TANGO (17) identified two potential aggregation-prone regions in EAS: residues L43-G51 and S71-A78 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several algorithms have been developed with the goal of predicting regions of protein sequence that have a high propensity for forming amyloid-like β-sheet polymeric structures. Given the evidence from X-ray fiber diffraction, electron microscopy, and Congo red and Thioflavin-T (ThT) binding that rodlets formed by class I hydrophobins are amyloid-like (15,16), we analyzed the amino acid sequence of EAS using several of these algorithms. TANGO (17) identified two potential aggregation-prone regions in EAS: residues L43-G51 and S71-A78 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of EAS, EAS Δ15 and EAS Δ15 -F72G monomers all suggest that residues T66-S71, in the N-terminal half of the Cys7-Cys8 loop, are highly mobile in solution on the nanosecond time scale (15,16). Therefore, it is likely that a conformational change involving a larger proportion of the Cys7-Cys8 loop can take place upon contact with a suitable interface.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, e.g., A␤, interfaces can give rise to alternative forms of fibrillar and nonfibrillar aggregates as determined by the nature of the interface (34). Finally, assembly of hydrophobins into functional amyloid-like rodlets occurs at an air-water interface (35). Thus, the choice of conditions is critical for understanding assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear Magnetic Resonance Spectroscopy-EAS ⌬15 isotopically labeled with 15 N was expressed and purified as described previously (16). 15 Circular Dichroism Spectropolariometry-CD measurements with DewA and ionic liquids were performed on an Applied Photophysics Chirascan Spectrometer at 24°C.…”
Section: Methodsmentioning
confidence: 99%
“…EAS ⌬15 is a truncated version of EAS, a class I hydrophobin from the bread mold Neurospora crassa, which forms amphipathic rodlets on the spore surface (14,15). We have determined previously the three-dimensional structures of the monomeric forms of both EAS and EAS ⌬15 and have demonstrated that the long Cys 3 -Cys 4 loop is not necessary for rodlet formation or stability (14,16).…”
mentioning
confidence: 99%